WORK ACCIDENTS IN THE BRAZILIAN FOREST SECTOR - Gomes Messias Viegas, Juliana; Carlos de Freitas, Luis; Pereira Santos, Rodrigo; Márcio Pinto Leite, Ângelo; César Fiedler, Nilton (Floresta, 2017)
This research aimed to evaluate occurrences of work accidents in theBrazilian forest sector involving activities of production of planted and natural forests, and forest support from 2010 to 2014 in order to carry out a diagnosis related to the safety and health of the worker. The sources for the data, collected from a literature research, were obtained based on historical data of the Company of Technology and Information from Social Security (DATAPREV). The results revealed that the activities of planted forests had the highest mean of accidents, followed by the forest support activities and the natural forests. States such as Minas Gerais, São Paulo, Paraná, Santa Catarina, Bahia, and Maranhão, for the greater extension in terms of planted forest areas, presented the highest mean of accidents in the sector during the period studied. By the Index Accident of Planted Forest (IAFP), the States of Mato Grosso do Sul, São Paulo, and Bahia had the highest average of occurrence of accidents (1,000 ha/planted forest) and the Minas GeraisState, the lowest one. The incidence rate of accidents in activities of planted forest and forest production support presented a frequency of occurrence higher than the Brazilian national average. The concessions of Social Security benefits for temporary disability (more than 15 days), permanent disability, and death in the forest sector caused to the Social Security an average spending of more than R 31 million. We concluded that the work accidents in this sector are significant and give rise to expenditures. Keywords: occupational safety, social security, occupational risks. Resumo Acidentes ocupacionais no setor florestal brasileiro. Objetivou-se, com esta pesquisa, avaliar as ocorrências de acidentes de trabalho no setor florestal brasileiro envolvendo as atividades de produção de floresta plantada, nativa e de apoio florestal no período de 2010 a 2014, com o intuito de realizar um diagnóstico relacionado à segurança e saúde do trabalhador. As fontes para a pesquisa bibliográfica dos dados foram obtidas com base em históricos da Empresa de Tecnologia e Informações da Previdência Social (DATAPREV). Os resultados evidenciaram que as atividades de florestas plantadas tiveram a maior média de acidentes, seguidas das atividades de apoio à produção florestal e de florestas nativas. Os estados de Minas Gerais, São Paulo, Paraná, Santa Catarina, Bahia e Maranhão, pela maior extensão em termos de áreas de florestas plantadas apresentaram a maior média de acidentes no setor no período estudado. Pelo Índice de Acidente de Floresta Plantada (IAFP), os estados do Mato Grosso do Sul, São Paulo e Bahia obtiveram a maior ocorrência média de acidentes para cada 1.000 ha de área plantada e o estado de Minas Gerais, o menor IAFP. A taxa de incidência dos acidentes nas atividades de floresta plantada e apoio à produção florestal apresentou frequência de ocorrência superior à média nacional brasileira. As concessões dos benefícios previdenciários para incapacidade temporária (superior a 15 dias), invalidez permanente e óbito no setor florestal ocasionaram à Previdência uma despesa média superior a R 31 milhões. Concluiu-se que os acidentes de trabalho nesse setor são significativos e ocasionam despesas. Palavras-chave: segurança do trabalho, previdência social, riscos ocupacionais.